"All in a Garden Green": Shakespeare's Staging of Garden Imagery. Issue 2 (November 2019) - Solomon, Deborah
Abstract : This essay draws attention to the surprising lack of scholarship on the staging of garden scenes in Shakespeare's oeuvre. In particular, it explores how garden scenes promote collaborative acts of audience agency and present new renditions of the familiar early modern contrast between the public and the private. Too often the mention of Shakespeare's gardens calls to mind literal rather than literary interpretations: the work of garden enthusiasts like Henry Ellacombe, Eleanour Sinclair Rohde, and Caroline Spurgeon, who present their copious gatherings of plant and flower references as proof that Shakespeare was a garden lover, or the many "Shakespeare Gardens" around the world, bringing to life such lists of plant references. This essay instead seeks to locate Shakespeare's garden imagery within a literary tradition more complex than these literalizations of Shakespeare's "flowers" would suggest. To stage a garden during the sixteenth and seventeenth centuries signified much more than a personal affinity for the green world; it served as a way of engaging time-honored literary comparisons between poetic forms, methods of audience interaction, and types of media. Through its metaphoric evocation of the commonplace tradition, in which flowers double as textual cuttings to be picked, revised, judged, and displayed, the staged garden offered a way to dramatize the tensions produced by creative practices involving collaborative composition and audience agency.